Effects of ethanol on the evaporation and burning characteristics of palm-oil based biodiesel droplet. (October 2021) - Chow, Ming Rong; Ooi, Jong Boon; Chee, Kong Meng; Pun, Chun Hoe; Tran, Manh-Vu; Kong Leong, Jeffrey Chin; Lim, Steven
Abstract: Palm biodiesel-ethanol blends could be the better automotive fuel over palm biodiesel alone owing to the high oxygen content and high volatility of ethanol. The evaporation and burning characteristics of palm biodiesel with 10%, 20%, and 30% ethanol by volume concentration respectively, were investigated by using the droplet experiment. Rapid bubble growth and bubble explosions during the heating stage were observed to be substantial for the palm biodiesel droplet added with 30% volume of ethanol (BE30). Adding ethanol in palm biodiesel increased the ignition delay and burn-rate constant by up to 38.6% and 23.2%, respectively whereas, the evaporation duration and burning period decreased by up to 20.6% and 22.5%, respectively. Overall, the relatively shorter evaporation duration and higher burn-rate found for the BE30 droplet could promote high thermal efficiency and has the potential to achieve ultra-low carbon monoxide (CO) and unburned hydrocarbons (UHCs) emissions in diesel and gas turbine engines. Highlights: Palm biodiesel-ethanol droplets exhibit more rapid bubble growth and explosion. Greater micro-explosion occurrences observed for palm biodiesel-ethanol droplets. The evaporation duration of palm biodiesel-ethanol droplets decreased significantly. The burn-rate and burning period of palm biodiesel-ethanol droplets improved.